PENGARUH PAJAK DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN DAN KOTA DI PROVINSI JAWA TENGAH (Students' Journal of Accounting and Banking, 2013)
This study aimed to examine the effect of tax and retribution regional to regional original revenue (PAD) the county and city in the province of Central Java. Tax and retribusi are one source of revenue that must continue to be extracted, enhanced, and managed by regional governments to finance local development for welfare and prosperity of the people. The sample in this study is the district and town in the province of Central Java have submitted the budget realization reports from 2007 to 2011 to the statistics central agency (BPS) in Central Java province. Based on these criteria, the sample used in this study were 175 counties and cities. Data of county and city then tested the normality that resulting data is not normally, so do the transformation of data and outliers and the number of samples to 99. It was also made multikolinierita, autocorrelation, and heteroskedastisitas test. After data showed normality and escaped from the classical assumption test, then was performed multiple linear regression test. The results of this study indicate that the taxe and retribution simultaneously and partially have significant positive effect to regional original revenue (PAD), so by increasing tax and retribution, the revenue also increased. Obtained adjusted R2 values for 0,950, this means that 95% PAD variation can be explained by variations from both the independent variable tax and retribution. While the remaining 5% is explained by other variables that are not included in the regression model. Keywords: regional tax, local retribution, PAD